(untitled) (Minerva, 2019)
Review: María Pilar Ciprés Torres, Guerra y sociedad en la hispania indoeuropea, Vitoria-Gasteiz, Servicio Editorial, Universidad del País Vasco, 1993, 216 pp. ISBN 84-7585-457-5